APPLICATION OF A DIFFERENTIAL APPROACH BASED ON LINGUISTIC MODELING IN PRIMARY EDUCATION - Djuraboyeva Zarnigor (Innovate Conferences, 2025)
This article analyzes the use of linguistic modeling methods in teaching grammatical concepts in primary education and the didactic possibilities of applying a differential approach in this process. While linguistic modeling allows for visual-form coverage of abstract language phenomena, the differential approach serves to improve educational effectiveness by taking into account students ' individual ability and level of training.
Keywords: primary education, grammatical concept, linguistic modeling, differential approach, methodology, didactic effectiveness